Antitumor effector B cells directly kill tumor cells via the Fas/FasL pathway and are regulated by IL‐10. Issue 4 (21st January 2015) - Tao, Huimin; Lu, Lin; Xia, Yang; Dai, Fu; Wang, Yi; Bao, Yangyi; Lundy, Steven K.; Ito, Fumito; Pan, Qin; Zhang, Xiaolian; Zheng, Fang; Shu, Guoshun; et al.
<x xml:space="preserve">Abstract</x> We have previously reported that adoptive transfer of tumor‐draining lymph node (TDLN) B cells confers tumor regression in a spontaneous pulmonary metastasis mouse model of breast cancer. In this study, we identified IL‐10‐producing cells within these B cells, and found that IL‐10 removal, either by using IL‐10−/− TDLN B cells or by systemic neutralization of IL‐10, significantly augmented the therapeutic efficacy of adoptively transferred TDLN B cells. Depletion of IL‐10 in B‐cell adoptive transfers significantly increased CTLs and B‐cell activity of PBMCs and splenic cells in the recipient. Activated TDLN B cells express Fas ligand, which was further enhanced by coculture of these TDLN B cells with 4T1 tumor cells. Effector B cells killed tumor cells directly in vitro in an antigen specific and Fas ligand‐dependent manner. Trafficking of TDLN B cells in vivo suggested that they were recruited to the tumor and lung as well as secondary lymphoid organs. These findings further define the biological function of antitumor effector B cells, which may offer alternative cellular therapies to cancer.